Matematyka
 
Brak innych książek z tego przedmiotu
 
Autorzy: Wojciech Babiański, Lech Chańko, Dorota Ponczek
Wydawnictwo: Nowa Era
Rok wydania: 2015
Uprość wyrażenie 4.67 gwiazdek na podstawie 6 opinii

  

 

 

 

 

 

 

 

 

 

`\ \ \ =1^2-(5y)^2-(1+10y+25y^2)=1-25y^2-1-10y-25y^2=-10y-50y^2` 

 

`e)\ (2x-y)(2x+y)+(3x+2y)(3x-2y)=((2x)^2-y^2)+((3x)^2-(2y)^2)=` 

`\ \ \ =(4x^2-y^2)+(9x^2-4y^2)=4x^2-y^2+9x^2-4y^2=13x^2-5y^2` 

 

`f)\ (y+3x)(3x-y)-(x-5y)(x+5y)=(3x+y)(3x-y)-(x^2-(5y)^2)=` 

`\ \ \ =(3x)^2-y^2-(x^2-25y^2)=9x^2-y^2-x^2+25y^2=8x^2+24y^2`